Efektivitas Sistem Informasi Akuntansi, Budaya Organisasi dan Kinerja Karyawan dengan Insentif dan Motivasi sebagai Variabel Moderasi - Sumantari, Ni Wayan Dina; Juliarsa, Gede (E-Jurnal Akuntansi, 2023)
The research objective was to determine the effect of the effectiveness of accounting information systems, organizational culture on employee performance with incentives, motivation as a moderating variable. The sampling method used was nonprobability sampling method with purposive sampling technique and 40 employees of the Srinadi Klungkung Market Cooperative were selected as samples. The data analysis technique used is moderated regression analysis. The results showed that the variable effectiveness of accounting information systems had a positive effect on employee performance, organizational culture variables had a positive effect on employee performance, incentive variables strengthened the effect of effectiveness of accounting information systems on employee performance, motivational variables strengthened the effect of effectiveness of accounting information systems on employee performance, incentive variables strengthened the influence of organizational culture on employee performance, motivational variables strengthen the influence of organizational culture on the performance of employees of the Srinadi Klungkung Market Cooperative. Keywords: Effectiveness of Accounting Information Systems; Organizational Culture, Incentives; Motivation; Employee performance.